2008
DOI: 10.1186/1752-1947-2-89
|View full text |Cite
|
Sign up to set email alerts
|

Managing a locally advanced malignant thymoma complicated by nephrotic syndrome: a case report

Abstract: IntroductionThe management of locally advanced inoperable malignant thymoma is difficult as there are no large randomized clinical trial data to guide treatment. However various case series have shown that malignant thymoma is often a chemosensitive disease. Cisplatin-based chemotherapy has been the gold-standard in the management of these patients. However when thymic cancers are complicated by paraneoplastic syndromes that damage kidney and neurological function, cisplatin use is often contraindicated.Case p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Next, we should consider limiting the use of cisplatin-based chemotherapeutic agents because of patients’ decreased renal function. In the case presented here, we applied cisplatin because the patient's renal function was in the normal range; however, some physicians have substituted carboplatin [21] or paclitaxel-based regimens for cisplatin. Finally, for secondary nephrotic syndrome, the management plan should be tailored by considering that secondary nephrotic syndrome has a chance to get better after management of the primary tumor with chemotherapy or surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we should consider limiting the use of cisplatin-based chemotherapeutic agents because of patients’ decreased renal function. In the case presented here, we applied cisplatin because the patient's renal function was in the normal range; however, some physicians have substituted carboplatin [21] or paclitaxel-based regimens for cisplatin. Finally, for secondary nephrotic syndrome, the management plan should be tailored by considering that secondary nephrotic syndrome has a chance to get better after management of the primary tumor with chemotherapy or surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…The current case conflicts with this proposal in some ways, since our patient had already been complicated with recurrent thymoma at approximately 9 months before the onset of the symptoms of nephrotic syndrome. Information about the onset of nephrotic syndrome during the course of advanced thymoma is limited ( 6 , 12 - 14 ), thus preventing us from evaluating the impact of this time lag on the overall disease process in the current patient. Nevertheless, we feel it is reasonable to consider that abnormalities in the immune system may result from thymoma as well as thymectomy, since the thymus is the primary stromal milieu guiding the maturation and selection of T-lymphocytes ( 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Steroid treatment appears to be well-tolerated and have acceptable benefits in select patients with thymoma-associated nephrotic syndrome due to MCD; however, previous studies demonstrating a good response to such a procedure are limited by their reliance on observational and retrospective data, making them vulnerable to confounding ( 6 , 7 ). Adjunct therapy with cyclosporine, cyclophosphamide, and/or chemotherapeutic agents has also been practiced in some patients in remission for nephropathy ( 14 , 19 - 21 ), but a lack of prospective data implies that the decisions made concerning therapy may be empirical. In the current case, the remnant state of the recurrent neoplasm as well as our failure to promptly perform tumor ablation with surgery, chemotherapy, and/or irradiation might have characterized the patient's overall response to the corticosteroids ( 3 , 22 , 23 ), and this might lead to the delayed or incomplete recovery from the AKI despite our failure to confirm histological characteristics compatible with interstitial edema and ischemic tubular injury, which can be pathogenic bases for the disease among patients with MCD ( 24 , 25 ), in the renal biopsy specimens.…”
Section: Discussionmentioning
confidence: 99%
“…However, we selected treatment with carboplatin due to the reduced risk of renal toxicity. While several reports have shown that standard-dose carboplatin-containing chemotherapy is effective for treating paraneoplastic nephrotic syndrome (10,11), no reports have demonstrated that standarddose carboplatin-containing chemotherapy is effective for treating paraneoplastic nephrotic syndrome in patients with lung cancer. In the present case, there were no adverse renal events during the administration of standard-dose carboplatin-containing chemotherapy, and the patient's nephrotic syndrome and renal dysfunction improved.…”
Section: Discussionmentioning
confidence: 99%